Synthesis and characterization of carbon nanotube from waste cooking oil using floating catalyst chemical vapour deposition method - Adnan, Noor Lyana (2017)
Research in nanotechnology is gaining interest due to its unpredictable nature and unique properties, making it one of the most research topic in the century. Due to the extraordinary properties of carbon nanotubes (CNTs), a lot of scientific research on the synthesize of CNTs structures have been studied around the world. The floating catalyst chemical vapor deposition (FCCVD) technique is a very promising and desirable technique for bulk CNTs cotton synthesis due to its simplicity, low cost and yield and does not require chemical processes to produce the final product. However, conventional CVD methods typically produce CNTs from carbon source which is available commercially such as ethanol. Disposing of used cooking oil becoming a problem because the solid waste regulations restrict the disposal of liquids in landfills. Subsequently unlawful disposal arises which includes open burning that causes black smokes, pouring down to drains that can clog the sewer system and eventually lead to unsanitary conditions. All this has disrupted the ecological environment, marine life and leading to global warming. Therefore, we have discovered a new method to produce bulk CNTs cotton using waste cooking oil as carbon source. The objective of this thesis is to synthesize CNTs using waste cooking oil as carbon source via FCCVD method. In this thesis single stage floating catalyst chemical vapor deposition (FCCVD) were used, the liquid hydrocarbon solution were waste cooking oil and ethanol (CH3CH2OH) as carbon source, ferrocene (C10H10Fe) as a catalyst and thiophene (C4H4S) as promoter, argon (Ar) and hydrogen (H2) as gas carrier. The liquid hydrocarbon solution is injected into a hot furnace along with hydrogen as carrier gas. Upon entering the furnace, these compound break down and react rapidly to form carbon nanotubes,which then interact to form a continuous cylindrical-shaped aerogel that is collected at the end of the tube reaction. In this thesis, production of CNTs cotton depends on various process parameters such as thiophene concentration, gas ratio of Ar:H2, ferrocene concentration, and liquid hydrocarbon solution flow rate were investigated. The morphology and structures of multiwall carbon nanotubes (MWCNTs) produced were characterized using Field Emission Scanning Electron Microscope (FESEM), High Resolution Transmission Electron Microscope (TEM), Thermo Gravimetric Analysis (TGA), X-ray Photoelectron Spectroscopy (XPS) and electrical properties were studied. Result reveal that the addition of 1.0 wt% thiophene to waste cooking oil causes a great increase on the amount of CNTs cotton obtained compared to that other concentration at 1150 °C. The ratio of Ar:H2 which was 400:300 sccm when using waste cooking oil as carbon source could cause more energy consumption, while it helps to achieve a high growth rate and aligned CNTs, due to the more presence of direct carbon precursor. As the concentration of ferrocene was increased by using ethanol as carbon source, causing the iron cluster to become bigger for the nucleation of CNTs. Concentration of 1.0 wt% and 1.5 wt% of ferrocene gave good morphological in structure and better properties. Lastly, high residence time, which is 5 ml/h liquid hydrocarbon flow rate by using ethanol as carbon source, may cause the excessive of carbon source supplement and accumulation of byproducts that lead to hybrid structure called graphenated carbon nanotubes. In conclusion, synthesize of CNTs using waste cooking oil were successfully carried out. Therefore, we provided an alternative idea for utilization of waste cooking oil to usable product for various applications in the future.